2012
DOI: 10.4236/mrc.2012.13007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Preparation Method on Co/Al<sub>2</sub>O<sub>3</sub> Catalyst Applied to Ethanol Steam Reforming Reaction Production of Hydrogen

Abstract: Alumina supported cobalt catalysts were prepared, characterized and applied in ethanol steam reforming for hydrogen production. The support and the supported catalysts were prepared, respectively, by the solvothermal and precipitation, impregnation and deposition-precipitation methods. The cobalt was added by impregnation and deposition-precipitation in the Al 2 O 3 supports using a Co(NO 3) 2 •6H 2 O solution. The solids were characterized, Temperature-Programmed Reduction with H 2 (RTP-H 2), X-Ray Diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The first one, with a maximum at around 340 °C, corresponds to the reduction of the Co 3 O 4 phase to CoO and a broad peak, centered at around 400 °C, corresponds to the reduction of CoO to Co 0 . Reduction peaks at above 700 °C, corresponding to the reduction of a mixed phase of cobalt oxide-aluminum oxide (non-stoichiometric aluminate) (Hu and Lu, 2010;Garcia and Assaf, 2012) reduction of surface CeO 2 , while the second peak is assigned to the subsequent reduction of CoO to Co 0 . Finally, the third peak at around 595 °C indicates the reduction of Co 2+ or Co 3+ ions in a strong interaction with CeO 2 , which could also inhibit the reduction of CeO x species.…”
Section: Characterization Of the Catalystsmentioning
confidence: 99%
“…The first one, with a maximum at around 340 °C, corresponds to the reduction of the Co 3 O 4 phase to CoO and a broad peak, centered at around 400 °C, corresponds to the reduction of CoO to Co 0 . Reduction peaks at above 700 °C, corresponding to the reduction of a mixed phase of cobalt oxide-aluminum oxide (non-stoichiometric aluminate) (Hu and Lu, 2010;Garcia and Assaf, 2012) reduction of surface CeO 2 , while the second peak is assigned to the subsequent reduction of CoO to Co 0 . Finally, the third peak at around 595 °C indicates the reduction of Co 2+ or Co 3+ ions in a strong interaction with CeO 2 , which could also inhibit the reduction of CeO x species.…”
Section: Characterization Of the Catalystsmentioning
confidence: 99%
“…They studied the cobalt catalysts supported on ceria, prepared by coprecipitation and impregnation methods, and found that the presence of easily reducible Co 3 O 4 on the ceria surface leads to a higher catalytic activity. Over 10%Co 3 O 4 /CeO 2 catalyst, ethanol conversion was close to 100% and H 2 selectivity was about 70% at 450 o C. Effect of the preparation method on cobalt catalysts applied to SRE process was also studied by Garcia and Assaf [53]. The authors pointed out that both the support synthesis method (solvothermal or precipitation) and the way of cobalt incorporation (impregnation or deposition-precipitation) were essential for obtaining efficient catalyst for the hydrogen production.…”
Section: Catalysts Performancementioning
confidence: 99%
“…The most often used supports for cobalt-or nickel-containing catalysts in the SRE process are oxides [5][6][7][8]. Alumina is one of the most widely used supports in catalysis due to its high surface area, which allows a great dispersion of the active phase [3], and its application as the support of cobalt-or nickel-based catalysts in the SRE process has been extensively studied [9][10][11][12][13][14]. However, the acidic character of alumina may promote ethanol dehydration to ethylene, which can lead to carbon formation on a catalyst surface.…”
Section: Introductionmentioning
confidence: 99%